Role of female-predominant MYB39-bHLH13 complex in sexually dimorphic accumulation of taxol in Taxus media. Issue 1 (14th March 2022) - Yu, Chunna; Huang, Jiefang; Wu, Qicong; Zhang, Chengchao; Li, Xiao-lin; Xu, Xinyun; Feng, Shangguo; Zhan, Xiaori; Chen, Zhehao; Wang, Huizhong; Shen, Chenjia
Abstract: Taxus trees are major natural sources for the extraction of taxol, an anti-cancer agent used worldwide. Taxus media is a dioecious woody tree with high taxol yield. However, the sexually dimorphic accumulation of taxoids in T. media is largely unknown. Our study revealed high accumulation of taxoids in female T. media trees using a UPLC–MS/MS method. Thereafter, many differential metabolites and genes between female and male T. media trees were identified using metabolomic and transcriptomic analyses, respectively. Most of the taxol-related genes were predominantly expressed in female trees. A female-specific R2R3-MYB transcription factor gene, TmMYB39, was identified. Furthermore, bimolecular fluorescence complementation and yeast two-hybrid assays suggested the potential interaction between TmMYB39 and TmbHLH13. Several taxol biosynthesis-related promoter sequences were isolated and used for the screening of MYB recognition elements. The electrophoretic mobility shift assay indicated that TmMYB39 could bind to the promoters of the GGPPS, T10OH, T13OH, and TBT genes. Interaction between TmMYB39 and TmbHLH13 transactivated the expression of the GGPPS and T10OH genes. TmMYB39 might function in the transcriptional regulation of taxol biosynthesis through an MYB-bHLH module. Our results give a potential explanation for the sexually dimorphic biosynthesis of taxol in T. media .